La décentralisation des services dans les petites villes indiennes, un enjeu technique et politique - Rémi de Bercegol; Shankare Gowda (Bulletin de l’Association de Géographes Français)
Through observing small municipalities, this paper questions new political and technical arrangements in small town governance in the aftermath of decentralisation reforms of basic services. In India, various research projects have dealt with these subjects in rural areas and large metropolises but little attention has been paid to the same issues in smaller urban settlements.